Fundamental features of AlCl4−-/AlCl4-graphite intercalation compounds of aluminum-ion-based battery cathodes. Issue 1 (23rd December 2022) - Li, Wei-Bang; Lin, Shih-Yang; Lin, Ming-Fa; Khuong Dien, Vo; Lin, Kuang-I.
Abstract : Up to now, many guest atoms/molecules/ions have been successfully synthesized into graphite to form various compounds. Abstract : Up to now, many guest atoms/molecules/ions have been successfully synthesized into graphite to form various compounds. For example, alkali-atom graphite intercalation compounds are verified to reveal stage-n structures, including LiC6n and LiM8n [M = K, Rb, and Cs; n = 1, 2, 3; 4]. On the other side, AlCl4 − -ion/AlCl4 -molecule compounds are found to show stage-4 and stage-3 structures at room and lower temperatures, respectively. Stage-1 and stage-2 configurations, with the higher intercalant concentrations, cannot be synthesized in experimental laboratories. This might arise from the fact that it is quite difficult to build periodical arrangements along the longitudinal z and transverse directions simultaneously for large ions or molecules. Our work is mainly focused on stage-1 and stage-2 systems in terms of geometric and electronic properties. The critical features, being associated with the atom-dominated energy spectra and wave functions within the specific energy ranges, the active multi-orbital hybridization in distinct chemical bonds, and atom- & orbital-decomposed van Hove singularities, will be thoroughly clarified by the delicate simulations and analyses.